Microstructural Changes during High Temperature Service of a Cobalt-Based Superalloy First Stage Nozzle - A. Luna Ramírez; J. Porcayo-Calderon; Z. Mazur; V. M. Salinas-Bravo; L. Martinez-Gomez (Advances in Materials Science and Engineering)
Superalloys are a group of alloys based on nickel, iron, or cobalt, which are used to operate at high temperatures (T > 540°C) and in situations involving very high stresses like in gas turbines, particularly in the manufacture of blades, nozzles, combustors, and discs. Besides keeping its high resistance to temperatures which may approach 85% of their melting temperature, these materials have excellent corrosion resistance and oxidation. However, after long service, these components undergo mechanical and microstructural degradation; the latter is considered a major cause for replacement of the main components of gas turbines. After certain operating time, these components are very expensive to replace, so the microstructural analysis is an important tool to determine the mode of microstructure degradation, residual lifetime estimation, and operating temperature and most important to determine the method of rehabilitation for extending its life. Microstructural analysis can avoid catastrophic failures and optimize the operating mode of the turbine. A case study is presented in this paper.